2022
DOI: 10.1186/s13005-022-00316-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional assessment of the favorability of maxillary posterior teeth intrusion in different skeletal classes limited by the vertical relationship with the maxillary sinus floor

Abstract: Background Understanding the anatomical relationship between the maxillary sinus floor (MSF) and the posterior maxillary teeth (PMT) is important when planning the orthodontic intrusion of the posterior teeth. This study aimed to determine the vertical relationship between posterior maxillary teeth and maxillary sinus floor in different skeletal classes in the Chinese adult population. Methods This is a retrospective cross-sectional study involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…So, we consider that the sinus cortex in this study was not intact in all cases, although not confirmed by histology. The maxillary apices of older subjects tended to be farther from the MSF, consistent with previous studies (38,40,41). The greater distance between the root tip and the MS with age appears to be a protective physiological response, increasing the distance between the MS and the increasing number of odontogenic infections that may occur, thus reducing the risk of MS abnormalities.…”
Section: Discussionsupporting
confidence: 88%
“…So, we consider that the sinus cortex in this study was not intact in all cases, although not confirmed by histology. The maxillary apices of older subjects tended to be farther from the MSF, consistent with previous studies (38,40,41). The greater distance between the root tip and the MS with age appears to be a protective physiological response, increasing the distance between the MS and the increasing number of odontogenic infections that may occur, thus reducing the risk of MS abnormalities.…”
Section: Discussionsupporting
confidence: 88%
“…However, the inferior wall of the maxillary sinus must be considered when intruding upper molars. The movement of posterior teeth across the maxillary sinus has been linked to moderate apical root resorption and increased tipping [57,58]. In our case, no movement of the zygomatic buttress miniplate or the buccal or palatal microscrews occurred neither during their use nor before clinical removal.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, the method can reflect the stresses, strains, and displacements in each part of the structure, especially the inner parts. The finite element method has progressed from simple 2D structural analysis to complex 3D structural analysis methods and has been widely applied in oral biomechanics [ 41 , 42 ]. Through in vitro experiments, we have learned about the mechanical and deformation characteristics of the maxillary sinus membrane [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%